Prediction of relative survival trends in patients with cutaneous squamous cell carcinoma using a model-based period analysis: a retrospective analysis of the surveillance, epidemiology, and end results database - Yong He; Ming Chen; Hai Yu; Wai-kit Ming; Jun Lyu; Suzheng Zheng; Jinrong Zhang; Wai Chi Lau; Hongtao Cheng; Hua Xian; Leong Nga Cheng; Shuli Huang; et al. (BMJ Open)
Objectives Cutaneous squamous cell carcinoma (CSCC) represents a malignancy characterised by the aberrant proliferation of skin epithelial cells, and certain instances of squamous cell carcinoma (SCC) exhibit features indicative of a heightened proclivity for recurrence, metastasis, and mortality. Tracking the latest survival rates for CSCC is crucial for patient care and public health strategies.Design This was a retrospective study.Setting The Surveillance, Epidemiology, and End Results (SEER) Programme database was established by the National Cancer Institute in 1973. It is one of the commonly used cancer databases in the United States, covering a variety of tumour types including lung cancer, breast cancer, gastric cancer, colorectal cancer, prostate cancer, etc. It collects cancer diagnosis, treatment and survival data for approximately 50% of the US population, providing systematic evidence support and valuable first-hand information for clinicians' evidence-based practice and clinical medical research. The data used in this study covers 20 years of information on patients with cutaneous squamous cell carcinoma from 2000 to 2019.Participants In this study, we identified a cohort of 2 04 055 patients, comprising 95 287 women and 1 08 768 men, who were diagnosed with CSCC between 2000 and 2019 in the SEER database. The inclusion criteria for this research encompassed individuals aged 15 years and older, availability of data spanning from 2000 to 2019, confirmation through microscopic examination, and the presence of a primary tumour classified as CSCC. Exclusion criteria involved cases solely validated through autopsy or a death certificate, those alive or with indeterminable survival times, and instances with incomplete data.Outcome measures The SEER database’s patient trends and relative survival rate for patients with CSCC were evaluated using period analysis method from 2000 to 2019. The anticipated 5 year relative survival rate among CSCC patients for the years 2020 to 2024 was projected using a generalised linear model.Results A total of 204,055 CSCC patients were identified, 95 287 women and 1 08 768 men. Most patients were male, white, lived in urban areas, presenting with localised metastases, aged 55–64 years, and had untyped CSCC. During the observation period, the 5 year relative survival rate of CSCC patients showed a slight improvement overall, while the 5 year relative survival rate of some subtypes showed obvious fluctuations. Particularly noteworthy was the substantial amelioration observed in the small cell nonkeratinizing SCC subtype, escalating from 60.4% in 2000 to 72.8% in 2019. The 5 year overall relative survival rates for CSCC patients during the intervals 2000–2004, 2005–2009, 2010–2014, and 2015–2019 documented rates of 62.4%, 63.4%, 64.3%, and 66.3%, respectively. Males had slightly lower survival rates than females, older patients had lower rates than younger patients, and white patients had better outcomes than non-white patients. Urban patients had higher survival rates than rural patients. Patients with distant metastases had significantly lower survival rates.Conclusion The temporal span from 2000 to 2019 witnessed a gradual yet delimited increase in survival rates among CSCC patients. This incremental trajectory persists, with a prognosticated survival rate of 67.1 anticipated between 2020 and 2024.